Discriminant analysis of concentrations of trace elements in Ulaanbaatar soil - Tsagaan, Byambasuren; Shabanova, Elena V; Vasil'eva, Irina E (Proceedings of the Mongolian Academy of Sciences, 2024)
In this work we investigated, through discriminant analysis, the spatial variability and pollution sources of potential toxic elements in Ulaanbaatar surface soil. The total concentration of potential toxic elements in urban surface soil samples, collected depending on pollution sources, were determined by using a rational scheme of chemical analysis of urban soils for ecological monitoring. It was found that the average concentration of B, Cr, Pb, Sn, Zn, Cu, Bi, Ag and Sb were all higher than their background values, while average concentration of Li, Ni, Co, V and Cd were comparatively lower. Urban surface soil samples had varying concentration levels of Ag, B, Bi, Cd, Cr, Cu, F, Ge, Mo, Pb, Sb, Sn and Tl, and identical levels of concentration of As, Co, Ni, Zn, Li, V and Mn. As per the results of the Kruskal–Wallis rank test, the surface soil in the ger (traditional round felt dwelling) area (A) and the main road (B) is highly polluted with Pb, Cu, Zn, Cr, MO, Sn, Bi, Ag and Sb. A stepwise selection of the spatial discriminant analysis shows that, Cr, Cu, Ge, Mo, Pb, Sb, Tl and V are most significant variables. These selected variables clearly discriminates the soil groups of the ger area (A) such as Khailaast, Chingeltei and Bayanzurkh, the main road (B) namely, along the central transport routes and in the vicinity of the bus stations and around the power plant and industrial area (C) with 71 per cent total success rate of classification.